HER2 as a target in invasive urothelial carcinoma. (26th February 2015) - Bellmunt, Joaquim; Werner, Lillian; Bamias, Aristotle; Fay, André P.; Park, Rachel S.; Riester, Markus; Selvarajah, Shamini; Barletta, Justine A.; Berman, David M.; de Muga, Silvia; Salido, Marta; Gallardo, Enrique; et al.
<x xml:space="preserve">Abstract</x> The association between HER2 status and overall survival (OS) in UC remains unclear. HER2 positivity may not only be a biomarker for more aggressive disease but also a potential therapeutic target. We report that HER2 overexpression or amplification in the primary tumor did not predict OS in patients with metastatic UC. Further trials in genomically screened patients are needed to assess HER2‐targeted therapies in UC.